EFEKTIVITAS PROGRAM PENDAFTARAN TANAH SISTEMATIS LENGKAP (PTSL) PADA KANTOR DESA MANGKUSIP KECAMATAN TANTA KABUPATEN TABALONG (JAPB, 2022)
Effectiveness of the Complete Systematic Land Registration Program (PTSL) at the Mangkusip Village Office, Tanta Tabalong District. Complete Systematic Land Registration is a land registration activity for the first time which is carried out simultaneously for all objects of land registration throughout the territory of the Republic of Indonesia in one village or other names equivalent to that, which includes the collection and determination of the correctness of biological data and juridical data. Concerning one or several objects of Land Registration for registration purposes. This study aimed to determine and analyze the Effectiveness of Complete Systematic Land Registration (PTSL) at the Mangkusip Village Office, Tanta District, Tabalong Regency. This study uses a qualitative descriptive approach; the data collection methods are observation, interviews, and documentation. The data analysis used is the Miles and Hubberman model. The results showed that the Complete Systematic Land Registration (PTSL) seen from the aspect of Usefulness was categorized as quite Effective, in the aspect of results was categorized as not yet Effective, and the aspect of Supporting Purposes was categorized as not yet Effective so that the conclusion of the study was Complete Systematic Land Registration (PTSL) at the Mangkusip Village Office. Tanta Subdistrict, Tabalong Regency is categorized as Ineffective. Keywords: Effectiveness, Registration, Complete Systematic Land (PTSL)